Molecular phylogenetic insights into the evolution of Eriosema (Fabaceae): a recent tropical savanna-adapted genus - Candido, Elisa Silva; Vatanparast, Mohammad; Vargas, Wanderleia de [UNESP]; Bezerra, Luisa M. P. A. [UNESP]; Lewis, Gwilym P.; Mansano, Vidal F.; Simoes, Andre O.; Silva, Marcos J.; Stirton, Charles; Tozzi, Ana Maria G. A.; Fortuna-Perez, Ana Paula [UNESP] (Oxford Univ Press, 2020)
Eriosema comprises c. 150 species and has a pantropical distribution and two centres of diversity, Africa and America. The species occur in tropical savannas and grasslands, including the cerrado in Brazil. They have adapted to these environments by developing specialized underground organs, and an abundance of trichomes. Here we present the first comprehensive molecular phylogenetic analysis of Eriosema, including species from its entire distribution range and generating 391 new DNA sequences. We sampled 140 species from nine genera of Cajaninae, of which 94 (60% of the genus) were Eriosema. Our analyses were based on the nuclear ITS and plastid rp132 and trnQ regions, and used maximum likelihood and Bayesian phylogenetic analyses of individual and combined data sets. In all analyses, Eriosema was resolved as monophyletic, but its interspecific relationships are not well resolved. Rhynchosia is not monophyletic, and some African Rhynchosia spp. emerged together as sister to Eriosema. Our study supports the monophyly of Adenodolichos, Dunbaria, Flemingia and Cajanus, but Chrysoscias and Bolusafra formed a dade that is sister to a group of Rhynchosia spp. Paracalyx was resolved as paraphyletic and nested among African Rhynchosia spp. Divergence time analysis suggested that the Eriosema lineages diverged 6.5-10.7 Mya. Two major lineages have diversified in Eriosema, one including most of the African species (4.41-6.68 Mya), the other mainly composed of the South American cerrado species (3.56-5.78 Mya). These results revealed that Eriosema is a recent and tropical savanna-adapted group, and its diversification occurred in the late Miocene in parallel with the expansion of C-4 grasslands.
Keywords: Cajaninae; cerrado; divergence time; grassland; Leguminosae; recent diversification; Rhynchosia; systematics